Micro, small, and medium enterprises business strategy: business sustainability during the covid-19 pandemic - Supeno, Bambang; Juliansya, Muhammad Farhan; Alhempi, R. Rudi; Shaddiq, Syahrial (Indonesian Indovisi Institute, 2025)
Indonesia has been hit by the coronavirus disease 2019 (COVID-19) pandemic since March 2020, but not only in Indonesia; some countries in the world are also experiencing the COVID-19 pandemic. This causes the economy to be unstable, which affects business people, including MSME players. The purpose of writing this article is how MSME actors are able to adapt during the COVID-19 pandemic in maintaining the sustainability of their business. The approach to writing this article uses qualitative and explained descriptively. The findings of this study are that the Government in its strategy can offer financial incentives based on advantages on fintech lending platforms, namely tax incentives, for fintech platforms that can provide direct access to funding for MSMEs, as well as MSME players in Indonesia in maintaining their business adapting by utilizing online media, such as twiter, facebook, istagram, gofood, gopay, wa group. This finding indicates the need for MSME actors to increase their strategies to adapt to the sustainability of their business during this pandemic.